UENF WS01: popcorn hybrid with water use efficiency for the State of Rio de Janeiro - Lima,Valter Jário de (2021)
Abstract The UENF WS01 is a hybrid that has an early cycle and high grain yield capacity under low water and nitrogen availability. It maintains popping expansion even under abiotic stress, thus being recommended for cultivation in the North and Northwest of the State of Rio de Janeiro.